Meprin β regulates osteopontin-signaling in ischemia/reperfusion-induced kidney injury - Faihaa Ahmed; Shaymaa Abousaad; Ayman Abouzeid; Christine Adhiambo; Elimelda Moige Ongeri (BMC Nephrology)
Abstract Background Meprin metalloproteases have been implicated in the pathology of ischemia/reperfusion (IR) induced kidney injury. Meprin β proteolytically processes several mediators of cell signaling pathways involved in apoptosis and extracellular matrix metabolism. We previously showed that meprin β cleaves osteopontin (OPN) in vitro. The objective of the current study was to determine how meprin β expression affects OPN and downstream mediators of the OPN-signaling pathway in IR-induced kidney injury. Methods Ischemia/Reperfusion injury was induced in wild-type (WT) and meprin β knockout (βKO) mice. Blood samples and kidney tissues were obtained at 24 h post-IR. The levels of OPN, Caspase-3, Bcl-2, and NFκB were evaluated using real-time PCR, western blot, and immunohistochemical approaches. Data analysis utilized a combination of 2-way ANOVA and unpaired t test. Results OPN mRNA increased in both genotypes at 24 h post-IR. Immunohistochemical staining showed IR-associated increases in the levels of OPN in both genotypes. Additionally, we observed higher levels of OPN in the lumen of proximal tubules in WT only, suggesting that meprin β contributes to enhanced release of OPN into filtrate and ultimately into urine. Immunohistochemical staining showed significant increases in the levels of Caspase-3 and NFκB in select tubules of WT only, while Bcl-2 staining intensity increased significantly in both genotypes at 24 h post-IR. Conclusions These findings suggest that meprin β modulates OPN levels in IR-induced kidney injury and impacts apoptotic genes regulated by the OPN signaling pathway. Clinical trial number Not applicable.